Orzecznictwo Europejskiego Trybunału Praw Człowieka a prawo do korespondencji skazanego i tymczasowo aresztowanego - Kwieciński, Adam; Chabier, Patrycja (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article focuses on the exercise of the right to correspondence by persons held in penitentiaries. The author’s analysis of the latest changes in this respect not only is based on the national regulations but is also performed in terms of their compliance with the standards of the European Convention on Human Rights and the case law of the European Court of Human Rights. A particular emphasis is put on the admissible restrictions in prisoners’ or detainees’ correspondence with their lawyers, public authorities, court authorities, legislators, law enforcement agencies and international organisations for the protection of human rights.
Keywords: korespondencja; cenzura; zatrzymanie; inwigilacja; zatrzymany; orzecznictwo Europejskiego Trybunału Praw Człowieka; Europejska Konwencja Praw Człowieka